Development of a thermoluminescence and radioluminescence integrated spectrometer. (February 2019) - França, Leonardo V.S.; Oliveira, Luiz C.; Baffa, Oswaldo
Highlights: An affordable thermoluminescence and radioluminescence spectrometer. Set-up construction relatively easy and straightforward. Ability of recording radioluminescence spectra as a function of the temperature. Abstract: The knowledge of the thermoluminescence and radioluminescence spectra is important for understanding the nature of luminescence emitted by thermoluminescent dosimeters and scintillators. In view of that, an instrument that records these two types of spectra was developed. Mechanical and structural parts as well as a description of each component of the instrument are described in detail. As part of the thermoluminescence spectrometer, a heating system was developed and details about all components involved, including electronics, are reported. The temperature ramps exhibited a good performance, reaching temperatures up to 500 °C with deviations up to 1 °C. The coupling of heating system with X-ray tube and optical fiber spectrometer enabled us to make radioluminescence and thermoluminescence spectra acquisitions. Furthermore, this arrangement demonstrated that thermal quenching of radioluminescence may be carried out. The development of the instrument showed to be relatively easy and straightforward, which can be manufactured by other research groups.